Effect of the DC-bias electric field on the phase transition characteristics in PMN ceramics - Lima, E. C.; Guerra, J. D.S.; Araujo, E. B. [UNESP] (Taylor & Francis, 2023)
Relaxor ferroelectrics play an important role for technological applications, mainly for using in the fabrication of actuators, transducers and sensors. Therefore, there has been an increasing interest of the scientific community in the investigation of the physical properties of such system in order to better elucidate the observed intriguing and unsolved phenomena. In this work, relaxor Pb(Mg1/3Nb2/3)O3 (PMN) ceramic system was prepared and the dielectric properties have been studied in details as a function of frequency, temperature and magnitude of the DC-bias electric field. Results reveal that the temperature dependence of the dielectric permittivity can be successfully described in the whole analyzed temperature range (100–400 K) by using a macroscopic statistical model, which describe the dielectric response in relaxor systems with diffuse phase transition (DPT). By using this phenomenological model, the temperature and DC-bias electric field dependences of the dielectric permittivity have been also revisited, from the analysis of the DPT behavior, promoting a careful discussion on the nature of the phase transition in relaxors materials. The calculated sizes of the polar nanoregions (PNRs) suggest the development of a structural disorder in the studied system, which promote the high diffuse ferroelectric transition as the amplitude of the DC-bias electric field increases.
Keywords: dielectric response; PMN; polar nanoregions; Relaxors